Unsuppressed serum albumin levels may jeopardize the clinical relevance of the international staging system to patients with light chain myeloma. Issue 5 (19th September 2018) - Kasamatsu, Tetsuhiro; Ozaki, Shuji; Saitoh, Takayuki; Konishi, Jun; Sunami, Kazutaka; Itagaki, Mitsuhiro; Asaoku, Hideki; Cho, Takaaki; Handa, Hiroshi; Hagiwara, Shotaro; Wakayama, Toshio; Negoro, Akiko; et al.
Abstract: The international staging system (ISS) is the most commonly used risk‐stratification system for patients with multiple myeloma (MM) and is determined by serum albumin and β2‐microglobulin levels. In the two determinants, β2‐microglobulin levels are frequently observed to be elevated in patients with myeloma, particularly in those with renal impairment. In comparison with patients with intact immunoglobulin myeloma, patients with LC myeloma do not necessarily show decreased levels of serum albumin. The clinical impact of ISS in patients with LCMM, in particular the distinction between ISS I and II, may be complicated due to non‐decreased levels of serum albumin in both stages. Accordingly, we have attempted to assess clinical relevance of the ISS in patients with LC myeloma. The clinical data of 1899 patients with MM diagnosed between January 2001 and December 2012 were collected from 38 affiliated hospitals of the Japanese Society of Myeloma. Significant difference was not found between stage I ( n = 72) and stage II ( n = 92) in LC myeloma patients ( n = 307). The mean serum albumin concentration of patients with LC myeloma was within the reference range but higher than that of patients with IgG + IgA myeloma ( n = 1501), which complicates the distinction between ISS stage I and II myeloma. Patients with LC myeloma had low frequencies of t(4; 14) and high frequency of elevated lactate dehydrogenase, and despite a relevant amount of missing data in our registry (R‐ISS stage I; n = 11, stage II; n = 32, and stage III: n = 18), the information included in the R‐ISS scoring system seems to be more accurate than ISS to obtain a reliable risk stratification approach in non‐ISS stage III LC myeloma patients.